Steel designers' manual - Davison, Buick; Owens, Graham W. (Graham Wynford); Steel Construction Institute (Great Britain) (Chichester, West Sussex, UK : Wiley-Blackwell, 2012)
'This classic manual on structural steelwork design was first published in 1955, since when it has sold many tens of thousands of copies worldwide. For the seventh edition all chapters have been comprehensively reviewed, revised to ensure they reflect current approaches and best practice, and brought in to compliance with EN 1993: Design of Steel Structures. The Steel Designers' Manual continues to provide, in one volume, the essential knowledge for the design of conventional steelwork. Key Features: Fully revised to comply with the new EUROCODE standards Packed full of tables, analytical design information and worked examples Contributors number leading academics, consulting engineers and fabricators'A must for anyone involved in steel design' - Journal of Constructional Steel Research'--
Pameran Fakulti/Nijuyon/Prof. Dr. Mohd. Raihan Taha
Includes bibliographical references and index.
Keywords: Building, Iron and steel -- Handbooks, manuals, etc; Steel, Structural -- Handbooks, manuals, etc